PEMAHAMAN LINTAS BUDAYA DALAM PEMBELAJARAN MEMBACA PADA MAHASISWA ANGKATAN 2021 - Widya Janatasya; Nana Rahayu; Yenny Aristia Nasution (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This study aims to describe the cross-cultural understanding of second-semester students of the Japanese Language Education Study Program FKIP Riau University Academic Year 2021/2022 on Tadoku's reading text. This study uses a qualitative descriptive research method to describe the competence of cross-cultural understanding in learning to read in 20 students from the class of 2021. The data for this research is Tadoku's reading text with the theme (Tsukimi 'seeing the moon'). Data collection techniques using tests. The instrument to be used in this research is in the form of an objective test, a true-false test, and a complete test. Item analysis data to determine the level of difficulty, validity, reliability, and the results will be analyzed by statistical descriptive analysis with the help of SPSS version 26. The results of the analysis using SPSS show that the questions have an easy level of difficulty, each item is valid without exception, and the questions are reliable. or consistent. Then, the results of the statistical descriptive analysis of students' understanding of the Tadoku reading text were at a moderate level. This can be interpreted that cross-cultural understanding of students affects the ability to understand the main ideas of student reading.Key Words: Understanding, Cross-cultural understanding, Tadoku.